1992
DOI: 10.2214/ajr.158.5.1566662
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant small round cell tumor of the abdomen: CT findings in five cases.

Abstract: Malignantsmall round cell tumor of the abdomen is a newly described clinicopathologic entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Intra-abdominal small round-cell tumours are very rare malignancies and only a few authors have reported series of more than five patients (Gerald et al, 1991;Varma et al, 1992;Ordofiez et al, 1993;Frappaz et al, 1994;Farhat et al, 1995). Here, we report our experience of multiple tumour marker screening in seven patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-abdominal small round-cell tumours are very rare malignancies and only a few authors have reported series of more than five patients (Gerald et al, 1991;Varma et al, 1992;Ordofiez et al, 1993;Frappaz et al, 1994;Farhat et al, 1995). Here, we report our experience of multiple tumour marker screening in seven patients.…”
Section: Discussionmentioning
confidence: 99%